Exploring food and nutrition security perspectives among high school adolescents in Machakel District, Amhara Region, Ethiopia: a qualitative study - Matyas Atnafu Alehegn; Mogessie Ashenafi; Mesay Mulugeta; Nigatu Regassa (BMC Research Notes)
Abstract Objective This study aimed to understand adolescents’ contextual perspectives on nutrition, food security, causes of food insecurity, and the association between food adequacy and academic performance. It explored food and nutrition security among high school adolescents in Machakel District, Amhara Region, Ethiopia. The objective was to explore how food and nutrition security impact adolescents’ growth and development. Qualitative data were collected through interviews with 33 key informants including school adolescents, teachers, health workers, community members, and woreda officers and six focus group discussions across four high schools. Data were analysed using MAXQDA Pro 2020 for its user-friendliness and advanced features. Results Findings showed that school adolescents living away from their families faced challenges in accessing adequate food, both in quantity and variety. These school adolescents relied on various strategies to access food, including part-time work and support from friends, relatives, or the school community, to supplement their food access. Participants perceived that inadequate food access negatively affected school adolescents’ academic performance. The study explored the need for interventions to improve adolescent food and nutrition security, including nutrition education programs, funding for nutritious school meals, and collaboration between schools and local communities to support adolescents living away from families.